Investigation of an acute chemical incident: exposure to fluorinated hydrocarbons. Issue 9 (1st September 2000) - Lyons, Ronan A; Wright, Dorothy; Fielder, Hilary M P; McCabe, Michael; Gunneberg, Andar; Nash, Pam; Routledge, Phillip; Rees, Huw
Abstract : OBJECTIVES: To assess whether attendance at the site after an incident in a sewer was associated with symptoms in emergency personnel and whether the prevalence of symptoms was associated with estimated levels of exposure to any chemical hazard. METHODS: Symptoms experienced by people attending an incident involving two dead sewer workers suggested the presence of a chemical hazard, before environmental sampling confirmed any toxic agent. Self reported symptoms, estimated exposures, and biomarkers of exposure for likely agents from all 254 people who attended the incident and a referent occupational group matching the 83 emergency personnel who went to the Accident and Emergency department (A and E) in the first 48 hours were recorded. The prevalence of symptoms and concentrations of creatine phosphokinase in serum of the 83 early patients at A and E were compared with their referent occupational group. In all workers who attended the incident, the trends in symptom prevalences and concentrations of creatine phosphokinase in serum were examined by distance from the site and predefined exposure category. RESULTS: Among all workers who attended the incident, symptoms of shortness of breath and sore throat were significantly associated with indirect estimates of exposure but not associated with concentrations of creatine phosphokinase. Freon was detected in two blood samples. The early patients at A and E reported more symptoms than their matched reference group and their median concentrations of creatine phosphokinase were higher. CONCLUSIONS: The association between symptoms and concentrations of creatine phosphokinase with attendance at the site indicated the presence of a continuing hazard at the site and led to extra precautions being taken. Comparison values from the referent occupational group prevented unnecessary medical follow up.